Neumonía bacteriana en paciente de sexo masculino de 67 años de edad - Velásquez Marin, Nelly Andrea (2020)
This clinical case study is focused on the health status of a 67-year-old male patient, who entered the emergency area presenting sudden symptoms of dyspnea with minimal effort, tachypnea, shortness of breath and cough with expectoration, with an oxygen saturation of 90%. Various procedures and techniques were used to monitor and obtain the definitive diagnosis in order to provide the corresponding treatment, resulting in bacterial pneumonia. Bacterial pneumonia is an acute but very serious pathology that causes the alveoli to become inflamed and fill with pus. Once diagnosed, it was treated with intravenous antibiotics such as (amoxicillin, ceftriaxone and clavulanic acid). The essential objective of this study is to establish the appropriate treatment according to the clinical picture presented by the patient. It was concluded that lung diseases such as bacterial pneumonia is a disease that affects people of all ages, hindering their respiratory function. Bacterial pneumonia can be acquired in the external environment or in a medical center, sometimes it can become more aggressive if there is a chronic underlying disease.